Tail dependence in emerging ASEAN-6 equity markets: Empirical evidence from quantitative approaches - Duy Duong; Toan Luu Duc Huynh (Financial Innovation, 2020)
This study contributes a rich set of quantitative methodologies including a non-parametric approach (Chi-plots and K-plots) as well as copulas (traditional and time-varying with Student's t-copulas) to the existing literature in terms of determining the dependence structure in ASEAN stock markets. Drawing on the emerging ASEAN equity returns of six countries from January 2001 to December 2017, we found that Student's t-copulas under time-varying approach is the most appropriate approach to explain these co-movements. Among all research return pairs, the dependence between Vietnam and other ASEAN equity indices has the lowest value. Meanwhile, all couples show left- and right- tail dependence by each pair for pre- and post- financial shocks. Hence, diversification across these pairs of equity markets from ASEAN is still adequate for international investors, though it might trigger contagion risks.
Keywords: 650; ASEAN; Stock indexes; Chi-plots; K-plots; T-copulas; Time-varying copulas